Análisis de la inversión en la obra pública de los GAD`S parroquiales del cantón San Miguel de Bolívar y su incidencia socioeconómica en la población. Caso GAD parroquial de Balsapamba año 2016 - Verdezoto Camacho, Lorena Jacqueline (2017)
The present investigation was carried out in the Parroquia Balsapamba, in order to analyze the investment in public works and its socioeconomic incidence in the population year 2016, also conducted surveys to 218 inhabitants, to know the efficiency of the works executed by the GAD ; and an interview with the president of the parochial GAD to know relevant aspects about the investments in works and the satisfaction of the settlers, whose main objective was to examine the current situation of the parochial GAD of Balsapamba, Bolívar Province, the results obtained show that the parochial GAD it must take advantage of the economic resources to carry out large-scale works, as well as to negotiate agreements with other institutions that generate a balance and economic sustainability to promote population development, taking advantage of the diversity of tourism; applying the chi-square test, the hypothesis is accepted where the works executed by the Balsapamba Autonomous Parochial Decentralized Government have a positive impact on the socioeconomic development of the inhabitants of the locality.